Analisa Perilaku Merokok pada Usia Produktif Terhadap Kesehatan di Wilayah Kerja Puskesmas Cilodong: Analysis of Smoking Behavior in the Productive Age on Health in the Cilodong Community Health Center Work Area - Alifiana, Winanda; Manenti, Dini Auliana; Cahyani, Intan; Rafsanjani, Naufal Muhammad; Sopian, Sabiha Mawaddah; Hakim, Achmad Lukman (MPI Press, 2023)
Background: Smoking is an unhealthy behavior, yet many people still engage in it, with some starting to smoke during their teenage years. In 2018, male smokers aged 15 years had the highest prevalence at 62.9%, and males remained the majority of smokers worldwide. Objective: To understand the general health status of the productive-age population in the working area of Cilodong Community Health Center in 2022. Method: This research uses a quantitative method with a descriptive approach. We obtained 121 respondents, and data were collected through the distribution of questionnaires. Results: Based on the health status, the top 10 diseases in Cilodong Community Health Center, Depok City, related to smoking behavior include hypertension. Conclusion: This analysis indicates that smoking behavior among the productive-age population in the working area of Cilodong Community Health Center is not favorable, as there is a significant number of individuals suffering from hypertension due to the influence of smoking.